EDUKASI PERAN LEMBAGA KEMASYARAKATAN DI DESA DALAM PEMBERDAYAAN MASYARAKAT DI DESA KRANGKONG - Isnaini Anniswati Rosyida; Ainul Masruroh; Ahmad Taufiq Rifaldi; M. Agus Heru Sulaksono; Erwin Mei Gumelang (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2021)
Abstract. Based on the findings, the authors conclude that Normatively supposed relationship with the Community Institutions Krangkong village government is to be a partnership as set out in legislation. But what happened in the field from local government is less active in the formation of social institutions so that the function of civil society as partners in empowering the village government does not run properly. As for the relationship between the Community Institutions in Rural Krangkong by decree No. 10 of 2016 is a partnership, consultation, and coordination. But the fact that of the seven social institutions studied, among others, RT, RW, Youth, PKK, KPM, LPMD, and Gopoktan, three community organizations of which only established but not running due to misunderstanding of the function of civil society itself. Then the village government strategies and institutions Krangkong kemsyarakatan Krangkong village is a need for the role of companion and extension remain in the village to make an association of villages Krangkong have steering activities within each work program. The village government Krangkong also need training and socialization of how to create regulations and technical skill training for the implementation of the village administration in the village Krangkong.